2012
DOI: 10.1002/eji.201142322
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid alleviates Con A‐induced hepatitis and differentially regulates effector production in NKT cells

Abstract: IntroductionLiver damage induced by various agents, such as viral infection, results in serious problems accompanied by an excessive immune response [1]. Uncontrolled severe responses in the liver by immune cells are observed in diverse animal models, including Con A-induced hepatitis. Following the administration of Con A, T cells, granulocytes, and Kupffer cells infiltrate into the liver, resulting in the death of hepatocytes [2][3][4]. NKT cells are responsible Correspondence: Prof. Chang-Yuil Kang e-mail: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…So, it mimics a number of human liver diseases in many respects, and is widely used as experimental animal hepatitis model to explore pathological mechanisms or evaluate treatment effects. Many studies showed that regulatory immune cells or molecules negatively regulated immune cells activation in liver, and alleviated Con A-induced liver injury (Erhardt et al, 2007;Lee et al, 2012;Tomiyama et al, 2011). These results suggested that maintaining immune homeostasis in liver is very important for hepatitis treatment.…”
Section: Introductionmentioning
confidence: 73%
“…So, it mimics a number of human liver diseases in many respects, and is widely used as experimental animal hepatitis model to explore pathological mechanisms or evaluate treatment effects. Many studies showed that regulatory immune cells or molecules negatively regulated immune cells activation in liver, and alleviated Con A-induced liver injury (Erhardt et al, 2007;Lee et al, 2012;Tomiyama et al, 2011). These results suggested that maintaining immune homeostasis in liver is very important for hepatitis treatment.…”
Section: Introductionmentioning
confidence: 73%
“…24 Also, it may be possible that NKT cells augment GVHD severity, 48 although there is no significant difference in the percentage of NKT cells from dnRARa and dnRARa-CD4…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic lymphocytes were isolated using Percoll (GE Healthcare, Little Chalfont, UK) as previously described (Lee et al ., 2012). Peripheral blood mononuclear cells (PBMC) were isolated using Histopaque‐1077 (Sigma‐Aldrich, St. Louis, MO, USA) following the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%